Link adaptation in closed-loop coded MIMO systems with LMMSE-IC based turbo receivers - Baozhu Ning; Visoz, Raphael; Berthet, Antoine O. (2014 International Conference on Computing, Networking and Communications (ICNC), 2014)
In this paper, we address the problem of link adaptation for closed-loop multiple-input multiple-output antenna systems employing iterative (turbo) linear minimum mean-square error (soft) interference cancellation and decoding. The link adaptation relies on a low rate feedback. It performs joint spatial precoder selection (e.g., antenna selection) and modulation-coding scheme (MCS) selection so as to maximize the average rate subject to a 10% target block error rate constraint. Each MCS is based on a bit interleaved coded modulation whose binary code is a punctured convolutional code. The paper first details the architecture of the turbo receiver then presents a semi-analytical performance prediction method to analyze its evolution through the stochastic modeling of each of the components. The prediction method is then used to derive the limited feedback metrics (precoder and MCS choice) used by the link adaptation algorithms. As the main contributions of the paper, the true impact of this family of iterative "turbo" receivers on the link level performance is measured. Monte Carlo simulations under limited feedback show a significant gain of around 3 and 4dB compare to the classical LMMSE receiver conditional on a data rate of 12 bits per channel use, for a 4x4 MIMO frequency flat and frequency selective channel, respectively. Moreover, they also confirm that using log a posteriori probability ratios rather than log extrinsic probability ratios on coded bits for soft interference regeneration and cancellation yields faster convergence of the iterative process and better final performance (both for finite and infinite interleaver length regimes).